Implementation of a Private Cloud for Sales Data Management Using Nextcloud at Dvapor Palembang - Achmad Alende Hudhuri (Jurnal Jaringan Komputer dan Keamanan, 2024)
The implementation of Nextcloud on Ubuntu provides an effective solution for building a secure and flexible private cloud storage system. As an open-source platform for file storage and collaboration, Nextcloud offers a robust and cost-efficient alternative to commercial cloud services. The implementation process on Ubuntu involves several essential steps, including system preparation, installation of required dependencies, and configuration of Nextcloud along with user access settings. These steps include installing LAMP (Linux, Apache, MySQL, PHP), downloading and installing Nextcloud, and configuring security parameters and access controls. In addition, backup setup and routine maintenance are necessary to ensure data integrity and operational continuity. Through Nextcloud, users can take advantage of features such as file synchronization, file sharing, and online collaboration while retaining full control over stored data. This implementation provides a customizable solution for organizations or individuals, enhancing operational efficiency and data security.